2020
DOI: 10.3390/ijerph17031089
|View full text |Cite
|
Sign up to set email alerts
|

Personality Factors and Sick Leave Days. Evidence from a Nationally Representative Longitudinal Study in Germany.

Abstract: Background: The question of whether employees’ sickness absence from the workplace depends on personality has been researched. Existing evidence mostly stems from cross-sectional studies, mainly showing that personality factors were not associated with the number of sick leave days, except for neuroticism, which was positively associated with sick leave days. Based on the above, it remains an under researched question whether intraindividual changes in personality factors are associated with changes in sick le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…The lack of any main effect of conscientiousness in our study was surprising, given earlier findings that conscientiousness is negatively related to work absence and the welldocumented health-and task-directed nature of conscientious individuals. Nevertheless, the other PERSONALITY AND SICKNESS ABSENCE 29 previous study on personality and register-based sickness absence also did not find an effect of conscientiousness (Blekesaune, 2012); neither did a study based on longitudinal survey data (Raynik et al, 2020). This could indicate that the potentially buffering effect of conscientiousness on work absence primarily appears for absenteeism and more short-term sick leave.…”
Section: The Prospective Associations Between Personality Traits and ...mentioning
confidence: 85%
See 2 more Smart Citations
“…The lack of any main effect of conscientiousness in our study was surprising, given earlier findings that conscientiousness is negatively related to work absence and the welldocumented health-and task-directed nature of conscientious individuals. Nevertheless, the other PERSONALITY AND SICKNESS ABSENCE 29 previous study on personality and register-based sickness absence also did not find an effect of conscientiousness (Blekesaune, 2012); neither did a study based on longitudinal survey data (Raynik et al, 2020). This could indicate that the potentially buffering effect of conscientiousness on work absence primarily appears for absenteeism and more short-term sick leave.…”
Section: The Prospective Associations Between Personality Traits and ...mentioning
confidence: 85%
“…Vlasveld and colleagues (2013) found that openness negatively predicted long sickness absence spells (> 2 weeks; medium effect size), but not short spells. The other studies that have examined personality dimensions and sick leave did not find an association with openness (Blekesaune, 2012;Raynik et al, 2020;Störmer & Fahr, 2013). Due to the sparse research on openness, it remains uncertain how openness and sickness absence are related.…”
Section: The Association Between Big Five Personality Traits and Sick...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our novel results based on the comparison of the FE models with the RE models suggest that the typically observed associations of employment sector and occupational exposures with SA may to a large extent be explained by unobserved individual characteristics. Underlying personal factors, eg, certain personality traits appear to influence both selection into particular work environments (39)(40)(41)(42) and having a high likelihood of SA (28,29,43). In addition, work attitudes and values have been found to influence selection into particular employment sectors (44)(45)(46) and these factors may also be associated with the use of SA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential causal mechanisms between work-related factors and SA, the associations may also be affected by selection, ie, individuals with characteristics associated with a high likelihood of fSA or pSA ending up in particular types of jobs. Most previous studies, however, have not been able to adequately control for such confounding, as many individual-level characteristics that are known to affect SA, eg, personality factors such as neuroticism ( 28 , 29 ), remain unobserved.…”
mentioning
confidence: 99%